Bureaucratic Innovation and Motivation in Implementing Programs and Activities (Study on the Implementation of Activities with a Limited Budget at the General Election Commission of the City of Probolinggo) - Dwi Putranto Riau; Rukin Rukin (Iapa Proceedings Conference, 2020)
For the Regency/City General Election Commission (KPU) that does not hold the 2020 Regional Head General Election (Pilkada), the annual budget is only sufficient for operational and personnel expenditure. The lack of operational budget led the KPU leadership to look for ways to make operational activities run with innovation and using the minimum budget or without the budget. This study aims to determine how programs and activities can run with minimal or no budget with innovation and motivation from leaders and staff. This research method uses qualitative methods with primary data collection techniques through in-depth interviews and secondary data through literature studies. The results showed that programs and activities could run with minimal or no budgets accompanied by strong motivation from the leadership and staff. The conclusion of this research is that programs and activities can run along with strong innovation and motivation.